Multi-fidelity assessment of exhaust systems for complete engine-airframe integrations - Hueso Rebassa, Josep; Tejero, Fernando; Otter, John J.; Goulos, Ioannis; MacManus, David G. (Unknown, 2020)
For podded underwing configurations, the goal of specific fuel consumption reduction has led to engine designs with larger fan diameters and higher bypass ratios to increase propulsive efficiency. As a consequence of this trend, the aerodynamic interference with the airframe is increased. Non-axisymmetric exhaust geometries could minimise such interference for coupled configurations. Class Shape Transformation functions are used to define 3D podded engine geometries that are installed on a transonic aircraft configuration. The complete system is assessed at mid-cruise conditions of a representative long-range cruise operation. The assessment is conducted by multi-fidelity computational fluid dynamics computations that are Euler inviscid and Reynolds Averaged Navier Stokes turbulent methods. The correlation between the different fidelities is analysed and a multi-fidelity co-kriging model is developed. The model is applied to predict the behaviour of installed non-axisymmetric exhaust systems and results into a 33% computational benefit compared to single-fidelity surrogates.
Keywords: Complete aircraft assessment; installed performance; non-axisymmetric exhaust systems; multi-fidelity analysis; co-kriging